Meeuwis 2020. A grammatical overview of Lingála - Kunzmann, Janika (AAeO - Afrikanistik-Aegyptologie-Online, 2022)
Meeuwis, Michael. 2020. A grammatical overview of Lingála: Revised and extended edition. Munich: Lincom.333 p., ISBN-10: 3969390044, ISBN-13: 978-3969390047; 158,00€